Characterization of Solid-State Complexities in Pharmaceutical Materials via Stimulated Raman Scattering Microscopy - Harju, Elina A; Tomberg, Teemu; Wurr, Lea; van Rijckeghem, Anneleen; Arbiol Enguita, Alba M; Dordovic, Vladimir; Johansson, Niklas G; Räikkönen, Heikki; Isomäki, Antti; Saarinen, Jukka K S; Gordon, Keith C; van Veen, Bert; et al. (Analytical chemistry, 2025)
In this study, we employed stimulated Raman scattering (SRS) microscopy, augmented with sum frequency generation, to characterize complex solid-state mixtures, containing many solid-state forms of the same compound, for the first time. Five crystalline forms and one amorphous form of lactose were characterized and resolved, including two more recently defined anhydrous solid-state forms. Additionally, the complex solid-state character of several commercially available pharmaceutical tableting and inhalation grades of lactose was profiled. The advanced multimodal label-free microscopy method enabled visualization of the distribution of the solid-state forms with submicron spatial resolution, including the detection of trace levels. In addition, quantitative solid-state compositions of the lactose products were estimated. Overall SRS microscopy allows sensitive and specific spatially resolved solid-state characterization of complex mixtures, beyond what is possible with established (nonspatially resolved) characterization methods.
Keywords: Tablets; tablety; Pharmaceutical Preparations; léčivé přípravky; nelineární optická mikroskopie; Spectrum Analysis, Raman; Microscopy; Lactose; laktosa; Nonlinear Optical Microscopy; mikroskopie; Ramanova spektroskopie